1990
DOI: 10.1901/jaba.1990.23-497
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Side Effects of Dro as Treatment for Self‐injurious Behavior

Abstract: A three-part controlled case study is presented in which severe and longstanding self-injurious behavior exhibited by a 9-year-old-boy was treated successfully with differential reinforcement of other behavior. In Phase 1, an experimental analysis demonstrated that the boy's scratching was not maintained by environmental contingencies; instead, it appeared that the self-injurious behavior was a stereotypic (automatically reinforced) response. In Phase 2, the effects of an escalating differentialreinforcement-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 13 publications
(10 reference statements)
2
62
1
1
Order By: Relevance
“…EXPERIMENT 2 Cowdery et al (1990) suggested that although continuous (noncontingent) access to stimulating activities may be effective in reducing stereotypic SIB, the intervention may not always be practical: These activities are not always available, they may require one-to-one supervision to ensure continued object manipulation, and they can lose their reinforcing effects due to satiation. In addition, continuous access to leisure materials might interfere with the performance of other adaptive skills.…”
Section: Leisure Materials Availablementioning
confidence: 99%
See 1 more Smart Citation
“…EXPERIMENT 2 Cowdery et al (1990) suggested that although continuous (noncontingent) access to stimulating activities may be effective in reducing stereotypic SIB, the intervention may not always be practical: These activities are not always available, they may require one-to-one supervision to ensure continued object manipulation, and they can lose their reinforcing effects due to satiation. In addition, continuous access to leisure materials might interfere with the performance of other adaptive skills.…”
Section: Leisure Materials Availablementioning
confidence: 99%
“…Cowdery et al (1990), for example, showed that access to a variety of games contingent on the nonoccurrence of scratching was an effective intervention, and Repp et al (1976) decreased the hair twirling, hand biting, and thumb sucking behavior of 3 children by delivering praise and edible reinforcers in a DRO contingency. Other studies have also shown DRO to be an effective intervention for treating stereotypic behavior (Luiselli & Krause, 1981;Repp, Deitz, & Speir, 1974).…”
Section: Leisure Materials Availablementioning
confidence: 99%
“…extinction has been associated with problems such as response bursting or emotional responding (see Lerman & Iwata, 1996, for a review), and similar negative side effects have been reported when DRO has been used to reduce problem behavior (Cowdery, Iwata, & Pace, 1990). By contrast, NCR has been reported to minimize the presence of side effects (Vollmer, Iwata, Zarcone, Smith, & Mazaleski, 1993;Vollmer et al, 1998).…”
mentioning
confidence: 92%
“…Even though this is a relatively simple behavioral method, its effects are possibly quite profound. This approach is similar to the procedure of differential reinforcement of other behavior (DRO) in which reinforcement is provided contingent on behaviors distinct from and absent of those targeted for reduction (for an applied example, see Cowdery, Iwata, & Pace, 1990). The result is potentially the increased frequency of the offender's desirable behavior with a simultaneous reduction in the frequency of aversive behaviors.…”
Section: Differential Reinforcementmentioning
confidence: 99%